Mathematical Modeling of Thin-Layer Solar Drying of Poultry Abattoir Sludge - Parlak, Nezaket; Ozdemir, Saim; Yetilmezsoy, Kaan; Bahramian, Majid (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
Drying of poultry abattoir sludge (PAS) in thin-layer procedure was investigated with solar drying during summer conditions (radiation intensity 415 W/m(2)) at 1, 2, and 5 cm of sludge depths and 0.00 and 2.00 m/s of air flow velocity with auxiliary solar heated air (60 degrees C) applied beneath the sludge layer under open surface drying conditions. Lower height of PAS together with hot air blowing from drying bed increased the drying rate and decreased the time required for achieving constant dry matter with equilibrium humidity below 10.0%. Hot air blowing significantly accelerated water evaporation from sludge particle and the drying period was reduced from 8 to 6 h with 2.00 m/s air flow intensity for the sludge depth of 1 cm. Seven established solar drying models were explored to characterize the drying behavior of PAS under thin-layer open surface solar drying conditions assisted with hot air blowing below the sludge bed. Among the implemented models, Page model and logarithmic model were found to best fit the results, respectively, for the experiments with ventilation (hot air blowing application) and without ventilation considering several statistical evaluators such as determination coefficient (R-2), sum of square error (SSE), and the square root of the mean squares of error (RMSE). Based on the achieved dry matter results, findings of this study demonstrated that the open surface solar drying assisted with solar heated air during high intensity solar radiation conditions could be an effective method for drying of PAS.
Keywords: Poultry abattoir sludge; Solar drying; Moisture; Modeling; Drying kinetics; SLAUGHTERHOUSE WASTE-WATER; MUNICIPAL SEWAGE-SLUDGE; MOISTURE DIFFUSION; AIR COLLECTOR; PERFORMANCE; BEHAVIOR; MANAGEMENT; KINETICS; PLANTS; DRYER; Environmental Sciences & Ecology